17. DO PROGESTERONE VALUES AFFECT THE EUPLOID RATE OF EMBRYOS IN PGT-A PATIENTS?. (August 2019) - García-Láez, V.; Labarta, E.; Mercader, A.; Delgado, A.; Bosch, E.; De Los Santos, M.J.
Abstract : Introduction: In about 35% of cases undergoing ovarian stimulation may occur a rise in serum progesterone in the late follicular phase. This could produce premature luteinization and affect the endometrial receptivity. However, some studies suggest that the elevated progesterone could generate damage to the oocyte affecting the embryo quality and therefore increasing the rate of aneuploidy in the generated embryos which contributes decrease the implantation and newborn live rate. Materials and Methods: A total of 2509 patients undergoing preimplantation genetic testing for aneuploidy screening (PGT-A) were included in this retrospective study performed between 2016 and 2018. The age of patients ranged from 22 to 49 years. Laser assisted blastocyst biopsies were done in all cases by either pulling or flicking method. Antagonist protocol was used in the majority of the cases and P4 levels were measured the day of hCG administration. Poisson regression model was used as statistical analysis where progesterone was considered as a continuous variable. Other variables such age, body mass index (BMI), estradiol and ovarian sensitivity index were included in the model. P values < 0.05 were considered statistical significant. Results: The increase of ovarian sensitivity index in one unit predicted the increase of euploid embryos in 1.67 times when controlling for the rest of variables. The increase in age had a negative influence decreasing the mean number of euploid embryos by 10%. On the other hand the increase of P4 values predicted an increase in the number of euploid embryos by 7%. Conclusions: The increasing values of progesterone does not decrease the availability of euploid embryos for transfer therefore, based in this initial approach P4 seems a surrogate marker of higher ovarian response which is also positively associated with embryo euploidy.